The priest, John Paul, waiting for Vince and Patricia Whiting
The priest, John Paul, waiting to administer the vows for Vince and Patricia Whiting at their sixth wedding. The wedding was held at the nursing home of Patricia's mother. Two unidentified guests are pictured in the background.